UV activated hollow ZnO microspheres for selective ethanol sensors at low temperatures - Chen, Yi; Li, Xiaogan; Li, Xiaoxin; Wang, Jing; Tang, Zhenan (Sensors and actuators. B, Chemical, 2016)
UV activated metal oxides for chemiresistive-type gas sensors have been recently studied aiming to lower the working temperature and thus lower the power consumption. In this work, the mesoporous hollow ZnO microspheres were prepared by template-assisted method and examined for VOCs detection with UV LED illumination at lower temperatures than 150°C. The as-synthesized ZnO based sensor indicated an excellent response and selectivity to different concentrations of ethanol (10–1000ppm) with low-powered UV LED (2mW) at 80°C. The response time is only ∼6s while the recovery is a little sluggish (∼94s). The enhanced sensing performance could be attributed to the mesoporous hollow microstructure of the synthesized ZnO and UV activated differential photoctalytic oxidation reactions at the shallow oxide surface regions. The repeatability and long term stability of the sensor and the sensor response were also investigated. A comparison with the conventional thermal-activated gas sensing of the hollow ZnO was also conducted and the photo-activated gas sensing mechanism was discussed.